MOTIVES FOR SOCIALLY RESPONSIBLE ACTIVITIES IN THE CONTEXT OF VALUE CREATION FACTORS: RESEARCH RESULTS (Polityki Europejskie, Finanse i Marketing)
The paper presents the results of an empirical study on the relationship between a company’s CSR activities and its performance. Most previous empirical investigations were focused on the interdependencies between CSR activity and metrics of value creation. However, this study adopted a different approach to the problem. Using the data obtained in the questionnaire, the study examined the relationship between CSR activity (its frequency) and the relevance of the benefits of responsible activities that directly or indirectly influence the value creation process. The main purpose was to verify the hypothesis that there are statistically significant interdependencies between companies’ CSR activities and the given benefits of responsible activities as value drivers. The result has shown that companies which are more involved in CSR activities (more regularly) tend to rank higher the benefits of CSR activities that are relevant value drivers